Petrological, Geochemical and Mechanical Characteristics of Kooz Kunarr Khewa Calcite Marble. (Global Journal of Science Frontier Research, 2022)
This methodical investigation s primary goal is to ascertain the geological geochemical mineralogical and mechanical characteristics of the calcite marble found in Khewa The article includes all important information about Khewa calcite marble including its quality constituent minerals related elements and other data The procedures employed for the precise investigation and evaluation of the mine s characteristics include manipulative field observation laboratory examination of Khewa calcite marble and preliminary library studies concerning the research location The calcite marble library research provided exact and accurate information about the location of the examined area s geology as well as information about its tectonics and magmatism In order for the laboratory analysis to determine the true geology of the area under study including adjacent rocks and the chemical makeup of the calcite marble laboratory examination is required Mica schist is the neighboring rock to calcite marble a metamorphic rocks The researcher gathered five random exact samples of the calcite marble from various locations in the field to acquire this For the desired outcomes various techniques were used on the assembled simples The purpose of XRF also known as XRay fluorescence is to determine the precise proportion of certain elements and oxides In addition to the calcite which is discovered in small amounts in the Mica schist rocks that surround the calcite marble in the XRF results the percentage of calcite is over 55 The Mica schist neighboring rocks of the calcite marble also contain a small quantity of uranium The unique characteristics of calcite marble such as their hues structures and linked minerals were elaborated by the microscopic analysis We obtained a range of results from physical and mechanical tests such compressive strength and unit weigh Wherever iron aluminum and nickel are found calcite marble is very hard Overall Khewa calcite marble is very hard but suitable for construction
Keywords: marble; calcite marble; tectonic; XRF; khewa; nangrhar